Student Performance in Mathematics in Portugal using PISA-2009 data - Susana, Faria (2016)
The Programme for International Student Assessment (PISA) is an international study launched by the Organisation for Economic Co-operation and Development (OECD) in 1997. It aims at evaluating education systems worldwide by assessing 15-year-olds' competencies in three key subjects (reading, mathematics and science) every three years. Studies based on PISA data to explain student performance are very common in literature. This paper is based on Portuguese data from PISA 2009, and it focus on the measurement of student achievement in mathematics and on the determinants of this achievement both at the student and at the school levels.